If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3.5x + 6) = 2.5x + -2 Reorder the terms: 2(6 + 3.5x) = 2.5x + -2 (6 * 2 + 3.5x * 2) = 2.5x + -2 (12 + 7x) = 2.5x + -2 Reorder the terms: 12 + 7x = -2 + 2.5x Solving 12 + 7x = -2 + 2.5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2.5x' to each side of the equation. 12 + 7x + -2.5x = -2 + 2.5x + -2.5x Combine like terms: 7x + -2.5x = 4.5x 12 + 4.5x = -2 + 2.5x + -2.5x Combine like terms: 2.5x + -2.5x = 0.0 12 + 4.5x = -2 + 0.0 12 + 4.5x = -2 Add '-12' to each side of the equation. 12 + -12 + 4.5x = -2 + -12 Combine like terms: 12 + -12 = 0 0 + 4.5x = -2 + -12 4.5x = -2 + -12 Combine like terms: -2 + -12 = -14 4.5x = -14 Divide each side by '4.5'. x = -3.111111111 Simplifying x = -3.111111111
| 2=9x | | 1/2x+4=-3 | | 0.6x=-7.2 | | x^2+y^2-9= | | (x-3)(3x+5)=0 | | 3/4-1/2b=3b | | 7x+5=13x+5 | | -8z-7=3z-7+5z | | x^2+3x-6=7x+6 | | -18-6=(1+3x) | | 23x-29y=7 | | 5x^2(6x+2)= | | 4x^2+4xy^2+y^4= | | 200=(50-2x)(20-2x) | | 6xz-5x= | | 2(a+12)=4 | | 2(x+4)=4+2x | | 18/12=m/42 | | 6d+5d=-11 | | 3x+2-4(8-7)=90 | | 10+x-1/3x+0 | | 35=-5+2g-7g | | b+27.51=36 | | -8n-3=-11 | | b/2-4=-8 | | -8n-3=-10 | | -8n-3=-83 | | x/2-5=-7 | | 2y^2-7y-15= | | 6x+45=9(x+5)-3x | | r/5+2=0 | | x/0.25 |